Hours of recreation, vol. III A collection of transcriptions for Violine (I and II), cello and piano - SINNHOLD, Rudolf (J. Fischer & Bro., 1906)
PrayernMelodienThe Gate of LifenOne Sweetly solemn thoughtnLargonAndante ReligiosonAve Maris stellanAwake my soulnReverie from KinderscenennAngels ever bright and fairnCalvarynAngels's dream